2013
DOI: 10.1111/aji.12106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tumor Necrosis Factor‐α on the Intracellular Ca2+ Homeostasis in Human Sperm

Abstract: Tumor necrosis factor-α decreases membrane permeability to Ca(2+) and affects Ca(2+) regulation in sperm cells in vitro, probably via lipid peroxidation, which may explain the decrease in sperm fertilizing capacity during inflammatory and infectious processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…As shown in the above, the effect induced by IFN-g on Ca 2+ permeability, was completely prevented in the presence of the antioxidant BHT. Similar results were found in human sperm using high concentration of TNF-a [Carrasquel et al 2013]. These results suggest that IFN-g oxidatively damages sperm membranes affecting the stability of some of the proteins that regulate Ca 2+ transport.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As shown in the above, the effect induced by IFN-g on Ca 2+ permeability, was completely prevented in the presence of the antioxidant BHT. Similar results were found in human sperm using high concentration of TNF-a [Carrasquel et al 2013]. These results suggest that IFN-g oxidatively damages sperm membranes affecting the stability of some of the proteins that regulate Ca 2+ transport.…”
Section: Discussionsupporting
confidence: 80%
“…However, a previous study demonstrated that IFN-g markedly reduced the activities of Na + -K + -ATPase, Ca 2+ -ATPase in sperm and decreased the rate of acrosome reaction [Bian et al 2007]. Additionally, we had previously observed that TNF-a (another cytokine), decreases membrane permeability to Ca 2+ and affects Ca 2+ regulation in sperm cells in vitro [Carrasquel et al 2013]. …”
Section: Discussionmentioning
confidence: 95%
“…In the testis, most of the germ cells undergo spontaneous degeneration during spermatogenesis and TNF-α determines the size of the germ cell population in the seminiferous epithelium by inducing germ cell apoptosis and disrupting Sertoli cell junctions as well as inhibiting steroidogenesis in Leydig cells (Lysiak, 2004 ). The high concentration TNF-α can alter intracellular Ca 2+ homeostasis by decreasing plasma membrane permeability to Ca 2+ (Carrasquel et al, 2013 ), whereas Ca 2+ signaling mediated responses are one of the main factors regulating sperm function (Publicover et al, 2007 ). Many studies reported that Ca 2+ signaling is involved in the regulation of dynein activity in mice sperm flagella (Lesich et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have proved that high cytokine levels may determine an alteration of sperm characteristics. [18][19][20][21] In our case, for the first time, we have detected increased amounts of proinflammatory cytokines directly in semen samples during infections by CagApositive H pylori strains, which could realistically be responsible for the reduced sperm quality observed in infected individuals. The proposed mechanism is supported by the observation that both cytokines showed significant a positive correlation with the percentage of necrotic sperm.…”
Section: Commentmentioning
confidence: 54%